2017
DOI: 10.1007/s12020-017-1322-5
|View full text |Cite
|
Sign up to set email alerts
|

MEN1 in children and adolescents: Data from patients of a regional referral center for hereditary endocrine tumors

Abstract: Purpose To retrospectively evaluate the age of onset of MEN1-associated lesions in a group of affected children and adolescents and to compare the clinical features of our series with the evidence derived from the literature. Methods The study population consisted of 22 Italian children and adolescents (age 6-31 years at the time of the inclusion in this study) all with a clinical and/or a genetic diagnosis of MEN1 performed before the age of 16 who have been followed-up regularly from 1998 to 2016 at the Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
(62 reference statements)
0
36
0
Order By: Relevance
“…Two recent studies analyzed series of adolescent patients with MEN1 ( 4 , 5 ). The study of Goudet ( 5 ) reported that 60.7% of their PHPT young patients (under the age of 21 years) underwent parathyroid surgery; 67.57% were operated by a PPTX/less than subtotal parathyroidectomy of only the affected glands and 32.43% by a STPTX; no TPTX was performed in their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies analyzed series of adolescent patients with MEN1 ( 4 , 5 ). The study of Goudet ( 5 ) reported that 60.7% of their PHPT young patients (under the age of 21 years) underwent parathyroid surgery; 67.57% were operated by a PPTX/less than subtotal parathyroidectomy of only the affected glands and 32.43% by a STPTX; no TPTX was performed in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Available data about clinical characteristics and therapeutic management of MEN1-PHPT during childhood and adolescence are principally derived from very few single case reports. Only two studies ( 4 , 5 ) on series of children and adolescents with MEN1 have recently been published. Both these studies confirmed PHPT as the most common and first clinical manifestation, also in young patients (58.3 and 73.8%, respectively), being asymptomatic in the great majority of cases (90.9 and 86%, respectively) and clinically diagnosed during yearly PHPT surveillance for MEN1 patients and/or for MEN1 gene mutation carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 11/22 children (median age 12) were asymptomatic at the end of the study. Eleven of the twelve children that did develop a manifestation of MEN1 were diagnosed with pHPT (Vannucci et al 2017). Another study shows that of the children and adolescents that develop MEN1-related disease before the age of 21 (n = 160), 75% (n = 122) has pHPT.…”
Section: Primary Hyperparathyroidismmentioning
confidence: 98%
“…Different clinical protocols have been recommended to allow the early diagnosis and treatment of MEN1-related tumors in MEN1 mutation carriers (1-7). Although the Clinical Practice Guidelines for MEN1 has recommended periodic vigilance initiating at 5, 8, and 10 years of age (1), respectively, for pituitary adenoma, primary hyperparathyroidism (HPT) and neuroendocrine pancreatic tumors, there are only a few papers emphasizing clinical features, management and treatment of children and adolescents with MEN1 (3,(8)(9)(10)(11)(12)(13).…”
Section: Editorial On the Research Topic Early Genetic And Clinical Dmentioning
confidence: 99%